Potencjał badawczy kategorii kognitywistycznych. W poszukiwaniu nowej formuły dyskursu edukacyjnego - Wiśniewska-Kin, Monika (Kultura-Społeczeństwo-Edukacja, 2019)
In order to describe in detail the differences between the discourse of a textbook and the discourse of children I used categories - applied in the area of cognitive considerations - concerning the language image of the world and the text image of the world, as well as selected sub-categories: point of view and perspective, type of rationality, method of categorizing, stereotypical and axiological overview of the reality. I assumed that the choice of categories and subcategories will not only allow to investigate the imposed meanings of the textbook discourse, but – above all – will make it possible to notice the very process of formation, the emergence of the image of the world from the perspective of children. The adopted analysis model launches reflection on the necessary changes, exposes the oppressiveness of the language of the textbook and encourages exploring the conditions to initiate the language of children.